Competency of Leaders in the Eastern Region Local Administrative Organization and Participation for Tourism Management - พิชิตนภากุล, ณิชกานต์ (Community and Social Development Journal, 2018)
This study aims to explain the relation between competencies of leaders in the Eastern Region Local Administrative Organization (LAO) and participation with tourism management at the overview level. Quantitative and qualitative data analysis are use. The quantitative data was gathered through questionnaire from 7 provincial leaders comprising Chanthaburi, Chonburi, Trat, Rayong, Prachinburi, Sa Kaeo, and Chachoengsao. Beside, the qualitative data was compiled through in-depth interview with personnel having significant roles in tourism management in the eastern region, and stakeholders. The findings revealed that self-assessment scores among leader competency topics show relative high scores in personal-related topics including understanding others, leadership, teamwork and service orientation, while, the criteria of achievement orientation, developing others, and Initiative gained moderate scores. Moreover, analysis on relation among each score and participation with tourism management found that competency topics related to participation directly, and gained high score, consisting of understanding others, leadership and teamwork. While the topics related to participation directly, but gained moderate score, including achievement orientation and Initiative. The author suggests that the leaders in the Eastern Region LAO should maintain the competency of understanding others, leadership and teamwork which are significant factors for regional tourism enhancement resulting from participation among LAO and relevant agencies. While, the policy makers should enhance understanding and awareness on achievement orientation for LAO leaders. Additionally, they should encourage leaders to gain initiative competency to allow participation in tourism management, not only just participation, but also truly drive goals achievement.